2022
DOI: 10.1108/ijssp-08-2022-0207
|View full text |Cite
|
Sign up to set email alerts
|

Initial social-policy responses to the COVID-19 pandemic in the Global North – A scoping review

Abstract: PurposeThe purpose of this scoping review is to analyse comparative studies on social-policy measures implemented during the COVID-19 pandemic in Global North welfare states. The authors also consider the potential influence of the regimes on the responses.Design/methodology/approachThe authors conducted a scoping review of six databases including peer-reviewed comparative studies. In an iterative process with exact inclusion criteria, the authors screened 699 titles/abstracts/articles and found 16 comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(229 reference statements)
0
7
0
Order By: Relevance
“…The experiences of blameful and stigmatising responses across the different nations included in this study were remarkably similar. This is perhaps unsurprising given that each state adopted similar pandemic management approaches which targeted citizens rather than the virus ( Jasanoff et al, 2021 ) and, in the first year of the pandemic at least, offered comparable social support to citizens ( Mäntyneva, 2022 ). Differences in broad governance structures did not impact strongly on stigma on the level of social interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences of blameful and stigmatising responses across the different nations included in this study were remarkably similar. This is perhaps unsurprising given that each state adopted similar pandemic management approaches which targeted citizens rather than the virus ( Jasanoff et al, 2021 ) and, in the first year of the pandemic at least, offered comparable social support to citizens ( Mäntyneva, 2022 ). Differences in broad governance structures did not impact strongly on stigma on the level of social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Each nation has different approaches to healthcare provision and operates under different welfare models. However, during 2020, the pandemic policies of the , , Germany and Japan broadly converged in terms of citizen access to healthcare services when severely ill with Covid and the provision of unemployment support benefits ( Mäntyneva et al, 2022 ). The longer-term impact of differences in social support across nations are explored by Qureshi et al (forthcoming – 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review of comparative studies showed that overall, social policy measures particularly in Europe have focussed mainly on the risk of unemployment and responses to the increased care-related needs of families due to COVID-19 (Mäntyneva et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Aidukaite et al ., 2021; Hick and Murphy, 2021; Béland et al ., 2021a, b; Bariola and Collins, 2021; Greve et al ., 2021; Pereirinha and Pereira, 2021). A review of previous studies (Mäntyneva et al. , 2023a) evidenced that while measures have been interpreted as strengthening the Nordic model in Nordic countries, for example, in Liberal welfare regime countries, the regime's effect on social policy measures has not been that clear.…”
Section: Introductionmentioning
confidence: 99%
“…From the outset of this decade, in the times of the COVID-19 pandemic, the share of public spending peaked in most OECD countries, which has led not only to austerity and economic adjustment measures, but also reforms and emphasis on welfare safety nets and proactive measures in various countries as crisis resilience. Social risks refer to traditional risks like health, unemployment, minimum income for a decent living (or last income support) and pensions (Mäntyneva et al. , 2023a, 2023b).…”
Section: Introductionmentioning
confidence: 99%